2007
DOI: 10.1136/ip.2007.016477
|View full text |Cite
|
Sign up to set email alerts
|

Association between road vehicle collisions and recent medical contact in older drivers: a case-crossover study

Abstract: Objective: To estimate the association between past medical contacts and the risk of vehicle collision in a population of older drivers from the province of Quebec, Canada. Design: Case-crossover study. Setting: Quebec. Participants: 111 699 older drivers involved in at least one vehicle collision between January 1988 and December 2000. Main outcome measures: For each driver, the risk of having a vehicle collision while exposed and not exposed to a medical contact was compared. Separate conditional logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A time window just before a RTC or RTI is considered the case period and a time window appropriately selected in the previous weeks or months is considered the control period for that case. Case-crossover studies, however, are only appropriate to study the effect of short-term exposures, such as the recent medical contacts4 or phone calls,5 on the risk of RTC.…”
Section: Introductionmentioning
confidence: 99%
“…A time window just before a RTC or RTI is considered the case period and a time window appropriately selected in the previous weeks or months is considered the control period for that case. Case-crossover studies, however, are only appropriate to study the effect of short-term exposures, such as the recent medical contacts4 or phone calls,5 on the risk of RTC.…”
Section: Introductionmentioning
confidence: 99%
“…The only screening strategy that may be feasible and effective in real conditions would be the single-test screening strategy for dementia, targeted at drivers aged 85 years and older seen in a primary care practice. However, in the absence of valid diagnostic tools, there are multiple barriers to formal assessment of driving competences of drivers with dementia Nevertheless, a recent study indicated that a medical contact, associated with an increased risk of crash in a population of older drivers from Quebec, could represent an opportunity to detect drivers potentially at risk 45 . However, the acceptability and feasibility for the primary care physician to use a battery of tests to detect inability to drive in all patients of various ages are likely to be low.…”
Section: Discussionmentioning
confidence: 96%
“…Physicians are important first-line actors in potential early detection programmes 27. They have the skills to assess the physical and psychological abilities of patients, and to discuss the positive and negative personal consequences of any post-screening interventions.…”
Section: Discussionmentioning
confidence: 99%